Fabrication of α-MnO2/UiO-66-NO2/TFC-PA Photocatalytic Membrane Applied for The Decomposition of Organic Dye In Aqueous Solution - Dung, Quach Manh; Tu, Nguyen Nang; Tan, Nguyen Xuan; Dai, Trinh Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 1DO - 10.25073/2588-1140/vnunst.5887, 2026)
In this research, α-MnO 2 /UiO-66-NO 2 /TFC-PA photocatalytic membranes were successfuly fabricatedy immobilizing α-MnO 2 /UiO-66-NO 2 catalyst onto the outer most surface of thin film composite polyamide (TFC-PA) membrane via interfacial polymerization process. The materials were characterized by using XRD, FTIR, EDX techniques. The photocatalytic activity was evaluated based on the decomposition of methylene blue (MB) solution under the visible light irradiation. The results showed that the highest MB removal efficiency was up to 95 %.  Factors affecting the efficiency of the decomposition were also investigated. The experimental results also displayed that the photocatalytic film has good regeneration ability, MB removal efficiency reached 92 % after 5 times and it can be facilely regenerated.